PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP EARNINGS PER SHARE - Kumala Shinta; Herry Laksito (Diponegoro Journal of Accounting, 2014)
The main purpose of companies are to increase and maximize the profit of the owners which form on Earnings Per Share (EPS). EPS shows how good the companies in giving return to the owners. In addition, in investing, EPS can be a main indicator to see the interesting point of stock. It because the amount of EPS will influence the price of stock in the market to get capital gain and to determine the amount of dividend. The research examines the influence of financial performance consisting of total asset turn over, current ratio, debt equity ratio, net profit margin, return on equity and price book value, firm size and operating cash flow on earnings per share. Research samples are Indonesian companies listedin the Indonesia Stock Exchange (IDX) in 2010-2012. Data used in this research are financial statements and Indonesian Capital Market Directory from Indonesia Stock Exchange (IDX). The data are analyzed by using multiple regression method with SPSS program. The analysis shows that total asset turn over, debt equity ratio, net profit margin, return on equity, price book value and operating cash flow have positive significant influence on earnings per share, while the firm size has negative significant influence on earnings per share. The result of this study also shows that there is no significant influence on the current ratio to earnings per share.